Effect of non-surgical periodontal therapy on CD14 + CD16+ monocyte counts in peripheral blood samples: a clinical interventional study - Raghunanthan Jagannathan; Thodur Madapusi Balaji; Suresh Ranga Rao; Meshal Saleh Alosaimi; Shankargouda Patil; Yuliia Siurkel; Marco Cicciù; Giuseppe Minervini (BMC, 2024)
Abstract Monocytes and their macrophage progeny are thought to be involved in tissue and alveolar bone destruction in periodontal disease. It has been documented that the proportion of (CD14 + CD16+) non-classical monocytes in the blood are elevated in chronic periodontitis;A total of 20 chronic generalized periodontitis patients who were otherwise healthy, were recruited for this study. At baseline and 3 weeks after non-surgical periodontal treatment, peripheral blood was obtained to assess the levels of C-reactive protein (CRP) and the proportion of monocyte subsets. Monocyte subsets were assessed using flow cytometry;The mean percentage of CD14 + CD16+ non-classical monocytes in the peripheral blood sample at baseline was 13.95 + 2.09, that reduced to 8.94 + 1.23 3 weeks after non-surgical treatment. A distinct significant reduction in the percentage of non-classical monocytes and a concomitant increase in classical monocytes were observed following periodontal treatment compared to baseline. There was a significant reduction in the all the periodontal parameters and CRP levels 3 weeks post non-surgical periodontal treatment. A positive correlation between CRP and percentage of non-classical monocytes was also observed; Periodontal treatment potentially modulates the host response effectively.